A favela e a lei: por um direito tolerante e protetivo (estudos aplicados sobre o Rio de Janeiro) - Ferreira, Allan Ramalho (2017)
This work, by Allan Ramalho Ferreira, entitled "The favela and the law: For a tolerant and protective right (applied studies on Rio de Janeiro)" is divided in three main chapters. The first aims to identify the hegemonic discourse about the favela, identifying it in the statements of the urban and secular legislations of the Rio de Janeiro State and the Rio de Janeiro Municipality, in particular from the stigmatizing turn that began with the choice of the city to host the Olympic Paralympic Games, which triggered a series of urban interventions and the outbreak of a real urban war, with police intervention and military bases installation in slums, in a planned socio-spatial segregation context - adoption of a dispersed city model. The second chapter analyzes with the democratic principle of urban relations analysis, emphasizing its procedural aspects, with the effective participation of slum dwellers in the urban policies formulation, implementation and monitoring, but also in a substancial approach, considering the minorities protection, in the face of the majority urban planning decisions, purposing formation of values towards city built diversities tolerance - foundations of a Community Urban Law. The favela is now taken no longer as an urban deviation, but as a place-in-the-city that receives the influxes of meanings and feelings attributed by its residents, seen beyond the territorial and discrimination stigma, based on the status of possession, so now as subjects of rights, empowered for city planning and (re) existence in the city, according to their desires and utopias (possible dreams). In the last chapter, we propose a shift in the analytic lens: from oppression to vulnerability. The vulnerability factors in the Rio de Janeiro favela removals are studied in order to specify the dwellers as rights subjects (vulnerable) with the incidence of the principle of equality. Thus, urban protection microsystems are formed, adopting the dialogue of the urban sources involved